Carbon and nitrogen stocks in sediment at Península Valdés Biosphere Reserve: novel insights into the potential contribution of large marine vertebrates to carbon sequestration - Jiménez-Ramos, Rocío; Egea, Luis G.; D’Agostino, Valeria C.; Degrati, Mariana; Loizaga, Rocío (Frontiers in Marine Science, 2025)
Although policymakers and stakeholders are beginning to acknowledge the importance of the marine biosphere in blue carbon services, the role of large marine vertebrates in the marine carbon and nitrogen cycle and especially in carbon sequestration has not yet been fully understood. Large marine vertebrates store only a small percentage of total oceanic carbon in their bodies, but they can provide important and lasting contributions to the oceanic carbon flux. The Península Valdés Biosphere Reserve in southwestern Argentina was partially established to conserve these large marine vertebrates, including the South American sea lion (Otaria flavescens) and southern right whale (Eubalaena australis). Three locations in Peninsula Valdés were sampling for the proximity of marine vertebrate populations in the area and the presence of salt marshes to assess the organic carbon (OC) and total nitrogen (TN) stocks in the top 1 m of sediment. Our work provides the first quantitative data on the OC and TN sequestered in the coastal sediments of Península Valdés and shows that this protected area contributes significantly to blue carbon by storing relevant quantities of OC (140 to 317 Mg OC ha-1) and nitrogen (7.3 to 22.9 Mg TN ha-1). Specifically, we found that salt marshes and terrestrial plants were the main C sources in each sediment core, but a non-negligible proportion (from 0.8 to 6.8% dry weight) of the OC stocks showed an isotopic signal from the large vertebrates that usually inhabit the area. Therefore, our results provide novel hypotheses about the potential contribution of large marine vertebrates as an OC vector in coastal systems and may serve as a basis for further investigation about their role into coastal blue carbon.